Baicalin, a Potent Inhibitor of NF-κB Signaling Pathway, Enhances Chemosensitivity of Breast Cancer Cells to Docetaxel and Inhibits Tumor Growth and Metastasis Both In Vitro and In Vivo - Zeng, Anqi; Liang, Xin; Zhu, Shaomi; Liu, Chi; Luo, Xiaohong; Zhang, Qinxiu; Song, Linjiang (Frontiers in Pharmacology, 2020)
Objective The aim of this study is to investigate the anti-cancer activity and sensibilization of baicalin (BA) against breast cancer (BC) cells. Methods The anti-proliferation of BA in BC cell lines was evaluated by MTT and colony formation assays. Apoptotic induction of BA was measured by flow cytometry. Wound-healing and transwell assays were exploited to assess migrated and invasive inhibition of BA. Western-blot and immunofluorescence were used to study mechanisms of anti-migration and sensibilization of BA. Anti-tumor and anti-metastasis effects of BA were evaluated in subcutaneous and pulmonary metastasis mouse model of BC cells. Results BA significantly suppressed proliferation and induced apoptosis of BC cells in a concentration- and time-dependent manner. Additionally, BA induced cell apoptosis via the mitochondria-mediated pathway, as evidenced by cellular induction of reactive oxygen species and upregulated expression of the Bax/Bcl-2 ratio. The overall expression and nuclear translocation of NF-κB signaling pathway in BC cells were dramatically inhibited by treatment with BA. BA significantly suppressed abilities of migration and invasion in BC cells. Notably, BA sensitized BC cells to docetaxel (DXL) by suppressing the expression of survivin/Bcl-2. BA also retarded tumor growth and triggered apoptosis of tumor cells in a tumor mouse model of 4T1 cells. Furthermore, pulmonary metastasis of BC cells was distinctly suppressed by BA in a tumor mouse model of 4T1 cells. Conclusion BA effectively triggered apoptosis, inhibited metastasis, and enhanced chemosensitivity of BC, implying that BA might serve as a promising agent for the treatment of BC.